MAKING A DOCUMENTARY VIDEO ON THE LOCATION OF JOGGING IN BATAM - Mangapul Siahaan; Justin Justin (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Documentary videos are videos that document reality while also providing educational and factual information. Making a documentary video requires a wide collection of material and a clear understanding of the topics that will be explored. In Batam, there is still no video that discusses the location of jogging in Batam City. Based on the background issues, the authors found useful goals and discussion topics to make a documentary video about the location of jogging in Batam utilizing the R&D research method and developed with the MDLC method. MDLC method is divided into several stages, namely: concept, design, material collection, manufacture, experiment and distribution. The author formulates the concept for a multimedia project that will be designed and developed, then begins the design process, which involves creating a storyboard to get a sense of the scenes that need to be captured. Afterwards, in the material collection stage, the author will collect the necessary materials such as audio back sound, location determination, plot arrangement. In the manufacturing phase, the author will use the collected material to create a documentary video, which will then be edited using software such as Adobe Photoshop, Adobe Premiere Pro, Adobe After Effects, and Adobe Audition. In the experimental stage, the output produced will be checked to ensure that it is appropriate, and then it will proceed to the distribution stage where the video will be uploaded to the SI study program YouTube. The end result is a video documenting the location of jogging in Batam.